Role of MIF Cytokine/CD74 Receptor Pathway in Protecting Against Injury and Promoting Repair - Farr, Laura; Ghosh, Swagata; Moonah, Shannon (Frontiers in Immunology, 2020)
Wound healing after an injury is essential for life. An in-depth understanding of the healing process is necessary to ultimately improve the currently limited treatment options for patients suffering as a result of damage to various organs and tissues. Injuries, even the most minor, trigger an inflammatory response that protects the host and activates repair pathways. In recent years, substantial progress has been made in delineating the mechanisms by which inflammatory cytokines and their receptors facilitate tissue repair and regeneration. This mini review focuses on emerging literature on the role of the cytokine macrophage migration inhibitory factor (MIF) and its cell membrane receptor CD74, in protecting against injury and promoting healing in different parts of the body.